A novel antagonist of p75NTR reduces peripheral expansion and CNS trafficking of pro-inflammatory monocytes and spares function after traumatic brain injury. Issue 1 (December 2016) - Lee, Sangmi; Mattingly, Aaron; Lin, Amity; Sacramento, Jeffrey; Mannent, Leda; Castel, Marie-Noelle; Canolle, Benoit; Delbary-Gossart, Sandrine; Ferzaz, Badia; Morganti, Josh; Rosi, Susanna; Ferguson, Adam; et al.
Abstract Background Traumatic brain injury (TBI) results in long-term neurological deficits, which may be mediated in part by pro-inflammatory responses in both the injured brain and the circulation. Inflammation may be involved in the subsequent development of neurodegenerative diseases and post-injury seizures. The p75 neurotrophin receptor (p75NTR) has multiple biological functions, affecting cell survival, apoptotic cell death, axonal growth, and degeneration in pathological conditions. We recently found that EVT901, a novel piperazine derivative that inhibits p75NTR oligomerization, is neuroprotective, reduces microglial activation, and improves outcomes in two models of TBI in rats. Since TBI elicits both CNS and peripheral inflammation, we used a mouse model of TBI to examine whether EVT901 would affect peripheral immune responses and trafficking to the injured brain. Methods Cortical contusion injury (CCI)-TBI of the sensory/motor cortex was induced in C57Bl/6 wild-type mice and CCR2+/RFP heterozygote transgenic mice, followed by treatment with EVT901, a selective antagonist of p75NTR, or vehicle by i.p. injection at 4 h after injury and then daily for 7 days. Brain and blood were collected at 1 and 6 weeks after injury. Flow cytometry and histological analysis were used to determine peripheral immune responses and trafficking of peripheral immune cells into the lesion site at 1 and 6 weeks after TBI. A battery of behavioral tests administered over 6 weeks was used to evaluate neurological outcome, and stereological estimation of brain tissue volume at 6 weeks was used to assess tissue damage. Finally, multivariate principal components analysis (PCA) was used to evaluate the relationships between inflammatory events, EVT901 treatment, and neurological outcomes. Results EVT901 is neuroprotective in mouse CCI-TBI and dramatically reduced the early trafficking of CCR2+ and pro-inflammatory monocytes into the lesion site. EVT901 reduced the number of CD45high CD11b+ and CD45high F4/80+ cells in the injured brain at 6 weeks. TBI produced a significant increase in peripheral pro-inflammatory monocytes (Ly6Cint-high pro-inflammatory monocytes), and this peripheral effect was also blocked by EVT901 treatment. Further, we found that blocking p75NTR with EVT901 reduces the expansion of pro-inflammatory monocytes, and their response to LPS in vitro, supporting the idea that there is a peripheral EVT901 effect that blunts inflammation. Further, 1 week of EVT901 blocks the expansion of pro-inflammatory monocytes in the circulation after TBI, reduces the number of multiple subsets of pro-inflammatory monocytes that enter the injury site at 1 and 6 weeks post-injury, and is neuroprotective, as it was in the rat. Conclusions Together, these findings suggest that p75NTR signaling participates in the production of the peripheral pro-inflammatory response to CNS injury and implicates p75NTR as a part of the pro-inflammatory cascade. Thus, the neuroprotective effects of p75NTR antagonists might be due to a combination of central and peripheral effects, and p75NTR may play a role in the production of peripheral inflammation in addition to its many other biological roles. Thus, p75NTR may be a therapeutic target in human TBI.